"Suspected killer": Tamar"s plight (Gn 38) as a lens for illuminating women"s vulnerability in the legal codes of Shona and Israelite societies - Mwandayi, Canisius (HTS teologiese studies, 2020)
The story of Judah and Tamar in Genesis 38 is one of the most intriguing stories in the Hebrew Bible. While it yields many useful insights into the character of God, the nature of sin and the aspiration of our redemption, it is equally offensive when one looks at it from a human rights perspective, considering, in particular, the vulnerable and defenceless woman, Tamar. Her being returned to her father’s house is portrayed as acting in accordance with the law for a childless widow (Lv 22:13; Rt 1:8). However, using the critical hermeneutical lens, it becomes apparent that the real motive that drove Judah to send her away was his fear lest his only surviving son Shelah should share the fate of Er and Onan, whose deaths he plainly attributed to Tamar’s doing. As such, Tamar was deprived of the right to marry Shelah as provided for in the levirate marriage law. Using feministic hermeneutics and the comparative approach, this article foregrounds the vulnerability experienced by women, especially when their husbands mysteriously or suddenly pass away. Because of the patriarchal hegemony of African and Israelite societies, childless widows often find themselves ostracised from the same families which they thought they were now part and parcel of by virtue of having married into that family. Much of the ostracism emanates from the fact that they are usually fingered as the prime suspects responsible for having played a part in their husbands’ deaths. Hence, the crux of this article is to present the interface between the Israelite and African worldviews, highlighting the parallels between the plight of widows in the Israelite and Shona societies.